Attitude of Social Media Users to Internet Advertising - Patricia E, CHIOMA; Ifedolapo, OMONIYI; Ernest E, ONUIRI (IJRDO-Journal of Applied Science, 2016)
The pervasiveness and wide use of social media has become a global phenomenon and hassince become a viable tool in promoting products and brands. It is in view of this that thisresearch seeks to ascertain the attitude of social media users to Internet advertising. Theadopted methodology is the descriptive survey with the target audience being college studentsof Covenant University, a privately owned faith-based institution of higher learning inSouthwest Nigeria. Results obtained showed that 100% of the social media users haveknowledge of Internet Advertising whereas 71.8% of the respondents actually pay attention tothe Internet adverts, hence suggesting that the Internet can be a good tool for brand promotion.Findings also reveal that 73% of respondents have at some point altered their purchase decisiondue to various adverts they have been exposed to on the Internet.